2022
DOI: 10.3389/fimmu.2021.760881
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influence on Frequencies of Myeloid-Derived Cell Subpopulations in Mouse

Abstract: Differences in frequencies of blood cell subpopulations were reported to influence the course of infections, atopic and autoimmune diseases, and cancer. We have discovered a unique mouse strain B10.O20 containing extremely high frequency of myeloid-derived cells (MDC) in spleen. B10.O20 carries 3.6% of genes of the strain O20 on the C57BL/10 genetic background. It contains much higher frequency of CD11b+Gr1+ cells in spleen than both its parents. B10.O20 carries O20-derived segments on chromosomes 1, 15, 17, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Krayem et al [ 30 ] identified a unique mouse strain, B10.O20, in the spleen, which showed a significantly higher frequency of myeloid-derived cells, such as CD11b + , CD11b + Gr1 + , CD14 + , and F4/80 + cells than other strains of mice. In that study, a bioinformatics analysis of genomic sequences indicated that Rab44 was a candidate gene for influencing the frequencies of immune cell subpopulations, since the mouse strain displayed different expression levels of Rab44 mRNA and a Rab44 gene mutation G275R, in which glycine at the position of the Rab44 gene was changed to arginine [ 30 ]. Therefore, it is likely that the Rab44 expression levels are involved in frequencies of immune-cell subpopulations in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Krayem et al [ 30 ] identified a unique mouse strain, B10.O20, in the spleen, which showed a significantly higher frequency of myeloid-derived cells, such as CD11b + , CD11b + Gr1 + , CD14 + , and F4/80 + cells than other strains of mice. In that study, a bioinformatics analysis of genomic sequences indicated that Rab44 was a candidate gene for influencing the frequencies of immune cell subpopulations, since the mouse strain displayed different expression levels of Rab44 mRNA and a Rab44 gene mutation G275R, in which glycine at the position of the Rab44 gene was changed to arginine [ 30 ]. Therefore, it is likely that the Rab44 expression levels are involved in frequencies of immune-cell subpopulations in mice.…”
Section: Discussionmentioning
confidence: 99%
“…We have sequenced the genomes of the strains BALB/c and STS using the next-generation sequencing (NGS) system HiSeq 2500 (Illumina, California, United States) (12× coverage) and analyzed them as described in (49,50). In detail, NGS data were preprocessed using the software Trimmomatic (51), and overlapping pair reads were joined by the software Flash (52).…”
Section: Detection Of Polymorphisms That Change Rna Stability and The...mentioning
confidence: 99%
“…Each CcS/Dem strain contains a different, random set of approximately 12.5% genes of the donor strain STS and approximately 87.5% genes of the background strain BALB/c (Demant and Hart 1986 ; Stassen et al 1996 ). B10.O20 carries 3.6% of genes of the strain O20 on the B10 genetic background (Krayem et al 2022 ). Strains were classified as resistant or susceptible according to their organ pathology and parasite load in organs (Lipoldová et al 2002 ; Sohrabi et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%